Great shakespearean tragedy : a criticism - Panigrahi, Dinesh (New Delhi Swastik Publications, 2012)
This book steers students through the critical writing on Shakespeare s tragedies from the sixteenth century to the present day. Patterns in Shakespearian Tragedy is an exploration of man s relation to his universe and the way in which it seeks to postulate a moral order. Shakespeare s development is treated accordingly as a growth in moral vision. His movement from play to play is carefully explored and in the treatment of each tragedy the emphasis is on the central moral theme. The book is written keeping in mind of Indian student of literature.